Smallholder Agriculture Monitoring and Baseline Assessment (SHAMBA) tool, Version 1.0 - Woolen E; Berry, N.; Cross, A.; Hagdorn M; Hughes M; Ryan CM (2014)
The SHAMBA (Small-Holder Agriculture Mitigation Benefit Assessment) model estimates greenhouse gas (GHG) emissions or removals resulting from a change in land management practices. SHAMBA is designed to model a baseline scenario (where land management activities continue as business as usual) and an intervention scenario consisting of activities that can be described as Climate Smart Agricultural practices (CSA) including, conservation agriculture, agroforestry and other tree planting. SHAMBA models the changes in carbon stocks in soils and woody biomass, and the GHG emissions from biomass burning, plant nitrogen inputs to soils, and fertiliser use over the accounting period for baseline and intervention activities. Net emissions and removals are calculated on a yearly basis for the length of the accounting period, in units of tonnes (t) of carbon dioxide equivalent (CO2e) per hectare (ha). Version one of the SHAMBA model is designed to work with smallholder systems and is available at https://shambatool.wordpress.com/outputs/.